Less Religion, Better Society? On Religion, Secularity, and Prosperity in Scandinavia - Lejon, Kjell (Dialog, 2011)
Phil Zuckerman argues in his book Society without God that Scandinavian secularity is strongly correlated to Scandinavian prosperity. In this article, we argue that such usage is premature. First, there are methodological issues that are not properly dealt with. Second, providing a causal narrative in addition to mere correlation is needed. Third, we argue that the causes of Scandinavian prosperity are found in close connection to Scandinavian Lutheranism.